PembuatanDye-Sensitized SolarCell (DSSC) menggunakan Kaca GMR sebagai Substrat dan Ekstrak Buah Naga (Hylocereus polyrhizus) sebagaiDye Sensitizer - Mafalocty, Vicie (RC-INSTITUT, 2019)
Dye-Sensisited Solar Cell (DSSC) is a photoelectrochemical solar cell that uses light energy for chemical reactions that produce electrical energy. In this study preparations of dye-sensitized solar cell (DSSC) using betalains extract of dragon fruit as natural dyes by varying the concentration of the dyestuff and the immersion time of ZnO electrodes in the dyes of dragon fruit. The results of UV-Vis spectroscopic analysis showed that dragon fruit maceration in methanol : HCl solvents had betalain pigments, where 2 maximum peaks are found, one is around 480 nm and the second is around 530 nm. FTIR spectroscopic analysis shows that the dragon fruit dye has a karbonil group so that the dye can bind well to the surface of ZnO. The results of testing the electrical properties show that the dragon fruit dye has enough LUMO energy level to inject electrons onto the surface of ZnO and has a HOMO energy level that supports the regeneration process of oxidized dye molecules. The results of the conversion of sunlight into electrical energy obtained the efficiency of variations in the concentration of dyes obtained maximum efficiency at 50% concentration of 0.41% and maximum efficiency of immersion time of 1.16% at the time of soaking 5 hours.